Functional reprogramming of regulatory T cells in the absence of Foxp3 - ÖZEN, AHMET OĞUZHAN (NATURE PUBLISHING GROUP, 2019)
Regulatory T cells (T-reg cells) deficient in the transcription factor Foxp3 lack suppressor function and manifest an effector T (T-eff) cell-like phenotype. We demonstrate that Foxp3 deficiency dysregulates metabolic checkpoint kinase mammalian target of rapamycin (mTOR) complex 2 (mTORC2) signaling and gives rise to augmented aerobic glycolysis and oxidative phosphorylation. Specific deletion of the mTORC2 adaptor gene Rictor in Foxp3-deficient T-reg cells ameliorated disease in a Foxo1 transcription factor-dependent manner. Rictor deficiency re-established a subset of T-reg cell genetic circuits and suppressed the T-eff cell-like glycolytic and respiratory programs, which contributed to immune dysregulation. Treatment of T-reg cells from patients with FOXP3 deficiency with mTOR inhibitors similarly antagonized their T-eff cell-like program and restored suppressive function. Thus, regulatory function can be re-established in Foxp3-deficient T-reg cells by targeting their metabolic pathways, providing opportunities to restore tolerance in T-reg cell disorders.
Keywords: TRANSCRIPTION FACTOR; DIFFERENTIATION; EXPRESSION; EFFECTOR; PHOSPHORYLATION; METABOLISM; TOLERANCE; MTOR; DEGRADATION; GLYCOLYSIS